Membangun Praktik Keagamaan Yang Inklusif Dan Dialogis: Telaah Terhadap Pendekatan Teologis Normatif - Muhammad Ghifary Ramadani Mallo (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
Religious diversity constitutes a fundamental aspect of the vibrant tapestry of interfaith life. Interreligious relations, often grounded in doctrinal teachings, serve as a foundation for the expression of individual beliefs and faiths. One such foundation is the normative theological approach, which emphasizes divine and normative values. However, this approach is frequently criticized for affirming the truth of a particular religious doctrine while excluding others. Therefore, it becomes essential to explore alternative or reconstructed frameworks that foster inclusive and dialogical religious practices, ultimately leading to harmony and peace. This study employs a qualitative research method to examine the normative theological approach and its implications for religious life. The findings suggest that while religious diversity continues to necessitate this approach to preserve the authenticity of religious teachings, it must be accompanied by inclusive and dialogical methods to avoid rigidity and exclusivity toward adherents of other faiths.